2006
DOI: 10.1017/s0950268806006686
|View full text |Cite
|
Sign up to set email alerts
|

Severity of infection and seasonal variation of non-typhoid Salmonella occurrence in humans

Abstract: SUMMARYNon-typhoid Salmonella infections may present as severe gastroenteritis necessitating hospitalization and some patients become septic with bacteraemia. We hypothesized that the seasonal variation of non-typhoid Salmonella occurrence in humans diminishes with increased severity of infection. We examined the seasonal variation of non-typhoid Salmonella infections in three patient groups with differing severity of infection : outpatients treated for gastroenteritis (n=1490) ; in-patients treated for gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The KauffmanneWhite scheme was used for serotyping of Salmonella. 26,27 Campylobacter was confirmed by microscopy and a positive oxidase and catalase reaction and identified as Campylobacter jejuni/coli, without differentiation between these two species.…”
Section: Charlson Comorbidity Indexmentioning
confidence: 99%
“…The KauffmanneWhite scheme was used for serotyping of Salmonella. 26,27 Campylobacter was confirmed by microscopy and a positive oxidase and catalase reaction and identified as Campylobacter jejuni/coli, without differentiation between these two species.…”
Section: Charlson Comorbidity Indexmentioning
confidence: 99%
“…We have previously shown that the typical seasonal variation of Salmonella infections with peaks occurring in August diminishes with increasing frailty in patient groups (Gradel et al, 2007); thus, the lack of difference in seasonal variation corroborates the minor role of host characteristics. On the other hand, this lack of difference is difficult to interpret in relation to exposure factors.…”
Section: Resultsmentioning
confidence: 55%
“…Categorical variables for Salmonella=Campylobacter coinfected, Salmonella monoinfected, and Campylobacter monoinfected patients were cross-tabulated and compared by odds ratios (OR) with 95% exact confidence intervals (CI), or, in case of zero counts, with 95% Cornfield CI. We assessed seasonal variation for the three groups as described previously (Gradel et al, 2007). In brief, we computed peakto-trough (PTT) ratios (i.e., the estimated incidence in the month of the peak divided by the 252 GRADEL ET AL.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Gastroenteritis is also seasonal since the quantity, the strains and the severity of the infection differ by season [10][11][12]. It follows, that any study that examines gastroenteritis should control for these effects.…”
Section: An Overview Of Gastroenteritismentioning
confidence: 99%